Not the Doctor’s Order; Eunuchs Access to Health Care in Central Punjab (Medical Forum Monthly, 2024)
Objective: The study aims to identify the barriers in availing healthcare services by eunuchs. Explore the needs and concerns, and ascertain the attitude of General Practitioners towards eunuch in providing health care services.Study Design: Descriptive / cross sectional study.Place and Duration of Study: This study was conducted at the University of Health Sciences, Lahore from April 2010 to march 2011.Materials and Methods: The total samples size was sixty. The group 1 included thirty eunuchsand group 2 included thirty General practitioners. A convenient non probability sample was identified from the target population. A questionnaire was used for the purpose of data collection.Results: Poor access to the doctor and non-availability of medicines were the most difficult part of seeking and receiving medical care. Use of unethical practices, lack of confidentiality, admission into male ward and death of colleague due to negligence were the negative experiences they came across while seeking medical care. Responding practitioners seemed to be bit uncomfortable in providing consultations to eunuchs in their clinics. Majority of the practitioners remained neutral to the question about their attitude toward hijras and agreed that it is more challenging to conduct genitourinary examination and also discuss sexual behavior with them.Conclusion: Hijras are neglected, discriminated against and not given the same rights as other Pakistanis, in matters of inheritance, employment, education and health care. This study reveals that marginalized population that have the health problems, both mental and physical and have the poor access to medical care. Similarly the health care providers are unable to provide appropriate care and devotion to these patients. There is a dire need to train health care providers to understand the psychosocial aspect of the Hijra culture and to deal with them without any prejudices. Health care policy makers must develop appropriate structures, policies and processes to enhance the social determinants of health so that equity in healthcare could be provided to all strata of the society.